Analytical study of the spiky feature in a two-photon driven lossy ladder system. (2nd September 2019) - Wang, Luojia; Xu, Jingping; Yuan, Luqi; Yang, Yaping
Abstract: There has been an experimental report (Traverso et al 2012 Proc. Natl Acad. Sci. USA 109 15185) that oxygen lasing in ambient air exhibits a spiky feature. We theoretically explore a ladder-type three-level atomic system driven by a two-photon resonant pump pulse in a lossy medium, which corresponds to that oxygen experiment. We study the Maxwell–Bloch equations both numerically and analytically and discover that a long pump field brings competition between two mechanisms of coherent pumping and coherent emission, leading to the spiky emission, which cannot be produced using a short pump. The results indicate that atomic coherence occurs in the experiment. Our study provides a clear understanding of the oxygen experiment using a nanosecond pump laser and could lead to the potential application of this oxygen lasing in future experiments.